2023
DOI: 10.3390/foods12193577
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Heavy Metal Dynamics in Soil and Honey: A Case Study from Maramureș Region, Romania

Florin Dumitru Bora,
Anca Cristina Babeș,
Anamaria Călugăr
et al.

Abstract: The study examined soil and honey samples from the Maramureș region, assessing potentially toxic elements and their concentrations. The highest concentrations were found for (Cu), (Zn), (Pb), (Cr), (Ni), (Cd), (Co), and (As), while (Hg) remained below the detection limit. Samples near anthropogenic sources displayed elevated metal levels, with the Aurul settling pond and Herja mine being major contamination sources. Copper concentrations exceeded the legal limits in areas near these sources. Zinc concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Generally, the dynamics of diverse elements, particularly heavy metals, are calculated between soil and plants [50,92], soil and honey [93] or plants (inflorescence) and honey [94,95]. Moreover, taking into consideration that the research carried out before on soils near some of our investigation areas [48,50,51,93] confirmed the presence of toxic elements and the transfer of these elements into plants, the objective of our study was to assess to what degree the main nutrients as well as toxic elements are transferred from plant to honey, specifically FJ plant and honey.…”
Section: Macro- Micro-and Trace Element Traceability In Fj Plant-hone...mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the dynamics of diverse elements, particularly heavy metals, are calculated between soil and plants [50,92], soil and honey [93] or plants (inflorescence) and honey [94,95]. Moreover, taking into consideration that the research carried out before on soils near some of our investigation areas [48,50,51,93] confirmed the presence of toxic elements and the transfer of these elements into plants, the objective of our study was to assess to what degree the main nutrients as well as toxic elements are transferred from plant to honey, specifically FJ plant and honey.…”
Section: Macro- Micro-and Trace Element Traceability In Fj Plant-hone...mentioning
confidence: 99%
“…This is primarily attributed to extensive anthropogenic activities, such as mining operations, involving the extraction of valuable metals and the processing of ores containing harmful substances such as Cd, Cu, Pb and Zn (the well- The northwestern region of Romania, in general, is renowned not only for its abundant underground mineral resources but also for being one of the country's most environmentally compromised areas, especially the Baia Mare depression and surroundings (Maramures , and Satu Mare county). This is primarily attributed to extensive anthropogenic activities, such as mining operations, involving the extraction of valuable metals and the processing of ores containing harmful substances such as Cd, Cu, Pb and Zn (the wellknown industrial platforms of Romplumb and Cuprom are examples in this case) [50,93,98].…”
Section: Research Location-descriptionmentioning
confidence: 99%
“…Honey samples were gently stirred while being warmed in the water bath to ensure even distribution (homogeneity) throughout the sample. Since honey dissolves readily in water, and metals can be directly measured in liquid solutions, honey samples are typically dissolved in water or a weak acid solution before analysis [16,48]. Following the initial sample preparation (involving ashing or digestion), the remaining residues are redissolved in either an acidic solution or ultrapure water.…”
Section: Analytical Approaches For Heavy Metal Analysismentioning
confidence: 99%
“…Following the initial sample preparation (involving ashing or digestion), the remaining residues are redissolved in either an acidic solution or ultrapure water. This step helps extract the metal components by breaking down the honey's organic structure and allowing the metals to transfer more efficiently into the solution for analysis [48]. To ensure consistent analysis, all honey samples were homogenized.…”
Section: Analytical Approaches For Heavy Metal Analysismentioning
confidence: 99%
See 1 more Smart Citation